CORPORATE CRIMINAL LIABILITY IN FINANCIAL CRIME CASES (CASE STUDY PT GARUDA INDONESIA (PERSERO) Tbk) - Madjid, Muhammad Nauval; Sitompul, M Nasir (Inspiring Law Journal, 2024)
The purpose of this research is to determine the roles and responsibilities of company management regarding financial crimes committed by their subordinates. To find out the challenges faced in enforcing corporate criminal liability in financial crime cases. To find out cooperation between law enforcement officials in handling financial crime cases. The nature of the research used is descriptive analysis leading to normative juridical legal research. The data sources obtained in this research come from secondary data, secondary data in the research comes from revelation data, primary legal materials, secondary legal materials, tertiary legal materials. Data collection tools in legal research usually use document studies. Based on research results, forms of financial crimes committed by corporations are Defrauding the Public (deceiving the public), Conspiracy in fixing prices, advertising products in a misleading way (misrepresentation of products), Defrauding the Government (deceiving the government), Transfer Pricing, Under Invoicing, Over Invoicing. The mode of financial crimes committed by PT. Garuda Indonesia Tbk, manipulated financial reports by recording sales transaction reports as compensation income for the rights to install connectivity and entertainment service equipment on board aircraft. In the end, Garuda Indonesia's financial report recorded a net profit. Criminal liability for financial crimes committed by PT. Garuda Indonesia Tbk was In the end, the Indonesian Stock Exchange (BEI) gave a written warning III and imposed a fine of IDR 250 million on Garuda Indonesia, as well as demanding the company to correct and present financial reports. Not only that, the Financial Services Authority (OJK) imposed a fine of IDR 100 million each on Garuda Indonesia and all members of the board of directors. OJK also requires companies to correct and restate their 2018 financial reports